THE ACTION AT ZOUTPANSDRIFT, 31 OCTOBER 1914 - Bouch, R.J. (Scientia Militaria - South African Journal of Military Studies, 2012)
Nine miles west of Brits, and five miles east of Bethanie, between Pretoria and Rustenburg, the Crocodile River flows past the Langberg. There are several drifts in the vicinity and of these Zoutpansdrift has given its name to an encounter between Government and rebel forces which ended in the surrender of 100 Government troops.